Nuestro Gramsci: Notes on Antonio Gramsci's Theoretical Relevance for the Study of Subaltern Latino Politics Research. Issue 4 (2nd October 2018) - Gonzales, Alfonso
Abstract : This essay draws on Antonio Gramsci's theoretical and philosophical insights to provide an alternative approach to mainstream Latino politics research that also introduces students to Gramsci. It contends that Gramsci provides a framework both for rigorously thinking about the challenges facing Latinos living in the United States and also for advancing an oppositional democratic politics in the face of the authoritarian turn in contemporary neoliberalism. Gramscian thought provides a theory and method for studying politics that can account for the structural conditions in which Latinos engage in politics, permitting the identification of dominant groups' methods of building consensus for authoritarian rule. Moreover, Gramscian theory provides analytical tools for conceptualizing an alternative approach to Latino politics research that is oppositional, theoretically driven, and grounded in a praxis focused explicitly on the empowerment of subaltern Latinos, such as the undocumented, refugees, indigenous "Latinos", Afro-Latinos, and LGBT Latinos, among others.